PELATIHAN STRATEGI HARGA PADA UKM - Arifin Djakasaputra; Yunia Arinda Jayanti (Transpublika Publisher, 2023)
Pricing refers to the process of setting the exchange rate of products that will be accepted by consumers. Factors affecting pricing include production costs, intended markets, competition, market conditions, and product quality. Price determination is a key concept in microeconomic theory and is one of the four elements of the marketing mix, Mitra which is the place of PKM activities is engaged in the egg nut snack business with the AMHR brand is located in Muaro Jambi. Through initial observations to business owner Mrs. Aminah through Whatshapp, there are main problems for partners in terms of determining selling prices that can increase competitive advantage. The results of PKM activities showed that the implementation of activities went smoothly, partners were eager to receive the material delivered by the PKM team. There is two-way communication between partners and PKM teams. In addition, outputs are made in the form of publications to journals and IPR.